(untitled) (Community Based Medical Journal, 2026)
Family planning programmes in Bangladesh have been successfully operating for decades; we achieved a phenomenal reduction in our fertility rates. This cross-sectional, descriptive study was conducted at Chandragram Village under Bajitpur Upazila of Kishoreganj District in Bangladesh, between January and December of 2023, to assess the awareness regarding family planning services among rural women. A total of 125 rural married women included in this study. Our sampling technique was convenience of non-probability type. The study revealed that the majority 52(54.4%) belonged to the 28–37 years age group. Most of them 51(40.8%) were married for >5 years. The majority 96(71%) had planned to use contraceptive in near future. Most of them 105(84%) were aware of social, economic and health problems of having more than two children. Regarding knowledge about family planning, 110(88%) had proper knowledge, while 89(74%) used different contraceptive methods. The majority 92(73.6%) were aware of failure of different contraceptive methods. 83(66.4%) had proper knowledge of importance regarding breast feeding in family planning. Most of them 94(75.2%) were satisfied with the family planning services. The majority 102(81.6%) told that government agencies have the responsibilities to make them more aware about family planning. This study presented a comprehensive overview of the awareness of family planning among the women of reproductive age group in rural Bangladesh. CBMJ 2026 January: vol. 15 no. 01 P:195-199